Application of Nursing Care for Pleural Effusion Patients in Pulmonary Ward - Aini Yusra; Syahrum; Abdul Gafar; Desi Deswita (Journal of Applied Holistic Nursing Science, 2026)
Background: Pleural effusion is a respiratory disorder characterized by abnormal fluid accumulation in the pleural cavity that may impair pulmonary expansion and gas exchange. Patients with pleural effusion commonly experience dyspnea, productive cough, decreased oxygenation, fatigue, and impaired activity tolerance. Appropriate nursing care is essential to improve respiratory function, maintain airway patency, and enhance patient comfort during hospitalization. Objective: This study aimed to describe the application of nursing care for pleural effusion patients in a pulmonary ward. Methods: This study used a descriptive case study design involving one patient diagnosed with pleural effusion in the Pulmonary Ward of Mohammad Natsir Regional Hospital, Solok City. Data were collected through interviews, observation, physical examination, and documentation review from April 2 to April 5, 2025. Data analysis was performed by comparing clinical findings with nursing theories, Indonesian nursing standards, and recent evidence-based literature. Results: The patient experienced shortness of breath, productive cough, weakness, and limited physical activity. Nursing assessment identified three primary nursing diagnoses, namely ineffective airway clearance, ineffective breathing pattern, and activity intolerance. Nursing interventions included airway management, oxygen therapy, effective coughing exercises, breathing pattern management, positioning, and energy conservation techniques. Evaluation results demonstrated improvement in respiratory status, reduction of dyspnea, decreased sputum accumulation, and better activity tolerance after the interventions were implemented. Conclusion: The application of comprehensive nursing care contributed positively to respiratory improvement and patient comfort in pleural effusion management. Early assessment, evidence-based respiratory interventions, and continuous nursing monitoring are important to optimize patient outcomes and prevent complications.